Decreased noradrenaline transporter density in the motor cortex of Parkinson's disease patients. Issue 6 (24th May 2018) - Sommerauer, Michael; Hansen, Allan K; Parbo, Peter; Fedorova, Tatyana D.; Knudsen, Karoline; Frederiksen, Yoon; Nahimi, Adjmal; Barbe, Michael T.; Brooks, David J.; Borghammer, Per
Abstract: Reduced noradrenaline levels have been reported to occur in the motor cortices of PD patients postmortem. Imaging techniques have recently become available to specifically study noradrenergic terminal function in vivo using PET. The objective of this study was to evaluate cortical 11 C‐MeNER binding in PD patients. Thirty PD patients and 12 healthy control subjects comparable in age, sex, and cognitive performance underwent PET imaging with 11 C‐MeNER, a specific ligand of the noradrenaline transporter. Cortical noradrenaline transporter binding was compared at a voxel level using Statistical Parametric Mapping, whereas cortical thickness was assessed using FreeSurfer software with MRI. PD patients showed reduced 11 C‐MeNER binding in the primary motor cortex unrelated to cortical thickness; other cortical regions did not differ between groups. In a subgroup analysis, patients with higher Hoehn & Yahr stage exhibited more pronounced 11 C‐MeNER binding reductions. Loss of cortical noradrenergic projections to the primary motor cortex occurs in PD associated with disease stage. © 2018 International Parkinson and Movement Disorder Society